Evaluation Of Performance Of Malaysian Banks In Risk Adjusted Return On Capital (Raroc) And Economic Value Added (Eva) Framework - Saha, Asish; Ahmad, Nor Hayati; Siew , Goh Yeok (Asian Academy of Management (AAM), 2016)
As Malaysian banks step into Basel-III era, a close look at their performance on risk adjusted basis using RAROC and EVA would throw significant light on their relative strengths and weaknesses. Post restructuring during 1999–2000, the regulatory framework of Bank Negara Malaysia (BNM) throughout 2001–2010 was mainly centered on capitalisation, risk management and governance practices in banks. Financial Sector Blue Print is viewed as the reference framework for growth of banks in the current decade. Though numerous studies have evaluated the performances of Malaysian banks in terms of efficiency and productivity gains before and after the merger and also at various phases during the last decade, no study has so far been reported to evaluate their performances using the above framework. This paper intends to fill up this gap. The period covered is 2001 to 2013. Findings of this paper would be of keen interest to the policy planners, investors and researchers alike.